Combining Oncolytic Viruses With Cancer Immunotherapy: Establishing a New Generation of Cancer Treatment - Shi, Tao; Song, Xueru; Wang, Yue; Liu, Fangcen; Wei, Jia (Frontiers in Immunology, 2020)
The recent successes of tumor immunotherapy approaches, such as immune checkpoint blockade (ICB) and chimeric antigen receptor T cell (CAR-T) therapy, have revolutionized cancer treatment, improving efficacy and extending treatment to a larger proportion of cancer patients. However, due to high heterogeneity of cancer, poor tumor cell targeting, and the immunosuppressive status of the tumor microenvironment (TME), combinatorial agents are required to obtain more effective and consistent therapeutic responses in a wide range of cancers. Oncolytic viruses (OVs) are able to selectively replicate in and destroy tumor cells and subsequently induce systematic anti-tumor immune responses. Thus, they are ideal for combining with cancer immunotherapy. In this review, we discuss the current understanding of OVs, as well as the latest preclinical and clinical progress of combining OVs with cancer immunotherapies, including ICB, CAR-T therapy, bispecific T cell engagers (BiTEs), and cancer vaccines. Moreover, we consider future directions for applying OVs to personalized cancer immunotherapies, which could potentially launch a new generation of cancer treatments.